Impact of dental caries and traumatic injuries on the quality of life of preschool children in urban and marginal urban educational institutions, Arequipa. - Hincho Vidal, Claudia Alejandra (2022)
Objective: To determine the impact of caries and dental trauma on the quality of life of pre-school children and their families. Material and Methods: Observational, cross-sectional study in 150 pre-school children from 3 to 5 years old of both genders of urban and marginal urban educational institutions. The parents signed the consent and answered the socio-economic file and the ECOHIS questionnaire (Early Childhood Oral Health Impact Scale) according to the perception of oral health related Quality of Life (QoL) of their children. Three examiners were calibrated, intra and inter-examiner agreement was measured, the result was Kappa 0.9. The clinical examination for caries and dental trauma was according to the criteria established by the WHO. The statistical analysis was performed by SPSS statistical package and spreadsheets. Dental caries was related to HRQOL (p <0.005 Anova), and dental trauma to HRQOL (p <0.05 U of Mann Whitney). Results: The domains with negative impact on ECOHIS were oral symptoms (20%) and parental distress (44.7%). The impact on the child section of the ECOHIS rural public schools presented a high average experience (14) and progression (1.47) of caries. While the impact on the family section, urban private schools were affect by dental trauma (66.7%). Conclusions: Caries generated a negative impact on children, families and HRQoL of pre-school children from rural public schools. Dental trauma only affected families in urban private schools.